Alasan Rusia Mengembangkan Senjata Nuklir Jarak Menengah (Intermediate Nuclear Forces) - Ardiansyah, Ruben Firman; Kumala Dewi, Putu Ratih; Nugraha, A.A Bagus Surya Widya (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL); Vol 2 No 2 (2023): Jurnal DIKSHI, 2023)
This research aims to explain Russia's interest in developing Intermediate Range Ballistic Missile that violates the Intermediate Nuclear Forces Treaty (INF Treaty). INF Treaty is an agreement that limited the use and development of ground missiles with a range of 500-5.500 km. INF Treaty played a big role in maintaining the stability of international security, mainly in the Euro-Atlantic region. After decades of the signing of this treaty, Russia has been confirmed to violate this treaty by developing missile 9M729, also known as SSC-8. This research used explanative qualitative method to explain Russia's interest, using data that were collected through literature review. The result of the analysis, using Offensive Realism theory, showed that structural changes in international order were causing the Russia to act offensive by developing  Intermediate Range Ballistic Missile.